Integrating WHO thinking healthy programme for maternal mental health into routine antenatal care in China: a randomized-controlled pilot trial - Nisar, Anum; Yin, Juan; Zhang, Jingjun; Qi, Wenli; Yu, Jie; Li, Jiaying; Li, Xiaomei; Rahman, Atif (Frontiers in Global Women's Health, 2025)
BackgroundWomen with perinatal depression and their children are at increased risk of poor health outcomes. Integrating evidence based non-stigmatizing interventions within existing health systems is crucial to reducing psychosocial distress during pregnancy and preventing perinatal depression. This study aimed to evaluate the feasibility of the World Health Organization (WHO) endorsed cognitive-behavior therapy-based Thinking Healthy Programme (THP), delivered by antenatal nurses in China.MethodsA two-arm pilot randomized controlled pilot trial was conducted to assess the feasibility and of the adapted Chinese version of the Thinking Healthy Programme (THP) among various stakeholders. We recruited pregnant women between 25- and 34-weeks' gestation from two pregnancy schools within the two public sector Hospitals in Xian. Participants in the intervention group attended five face to face sessions of THP facilitated by antenatal nurses. This intervention used cognitive behavior therapy principles to offer psychoeducation, behavioral activation, problem-solving strategies, and social support. In the control group, participants received standard care, which included routine pregnancy education classes led by antenatal nurses. We assessed depressive symptoms using the Patient Health Questionnaire-9 (PHQ-9) at baseline, after the intervention and 4–6 weeks post-intervention, along with evaluations of anxiety, perceived social support, and health-related quality of life.ResultsAmong the 737 pregnant women screened, 267 (30.26%) scored ≥5 on the PHQ-9. Out of these, 85 were eligible and consented to participate, with 42 assigned to the intervention group and 43 to the control group. Eighty participants (94.1%) completed the final assessments. Our primary findings indicated that this nurse-delivered intervention was feasible to integrate into routine antenatal care and was well-received by both the women and the delivery agents. Although the study was not designed to detect differences between the intervention and control groups, we observed positive trends towards reductions in anxiety and depressive symptoms favoring the intervention arm. No serious adverse events were reported. This trial is registered in the Chinese Clinical Trial Registry with the registration number ChiCTR1900028114.ConclusionsWe conclude that this intervention, grounded in the well-established WHO Thinking Healthy Programme, is both feasible and acceptable to stakeholders. It merits a definitive randomized trial to assess its effectiveness and cost-effectiveness across various settings.Clinical Trial RegistrationChiCTR1900028114.